INCREASING ACCESS IN ONLINE HIGHER EDUCATION - Bourne, John; Moore, Janet C.; Sener, John; Mayadas, Frank; Ettinger, Linda F. (Online Learning, 2006)
This paper investigates how access to higher education in the United States can be increased through further integration of online education. The search for opportunities to increase access to online education examined multiple prospective higher education contexts. A series of papers produced by participants in the 2005 Sloan-C summer workshop is synthesized and presented in this overview. Individual papers are included in the publication, providing analyses of specific opportunities.